Behavioral Profiling in Early Adolescence and Early Adulthood of Male Wistar Rats After Short and Prolonged Maternal Separation - Lundberg, Stina; Nylander, Ingrid; Roman, Erika (Frontiers in Behavioral Neuroscience, 2020)
Early-life stress and its possible correlations to genes, environment and later health outcomes can only be studied retrospectively in humans. Animal models enable the exploration of such connections with prospective, well-controlled study designs. However, with the recent awareness of replicability issues in preclinical research the reproducibility of results from animal models has been highlighted. The present study aims to reproduce the behavioral effects of maternal separation (MS) previously observed in the multivariate concentric square field (MCSF) test. A second objective was to replicate the adolescent behavioral profiles previously described in the MCSF test. Male rats, subjected to short or prolonged MS or standard rearing, were subjected to behavioral testing in early adolescence and early adulthood. As seen in previous studies, the behavioral effects of MS in the MCSF were small at both tested time-points. When tested in early adolescence, the animals exhibited a similar behavioral profile as previously seen and the finding of adolescent behavioral types was also reproduced. The distribution of animals into the behavioral types was different than in the initial study, but in a manner consistent with developmental theories as the current cohort was younger than the previous. Notably, the Shelter seeker behavioral type persisted through development while the Explorer type did not. The lack of basal behavioral effect after MS is in line with the literature on this MS paradigm; the working hypothesis is that the prolonged MS gives rise to a phenotype predisposed to negative health outcomes but which is not apparent without additional provocation.